Development of a Method to Enhance the Efficiency of Establishing VR Educational Laboratories - Ikromjon, Rakhmonov; Rayhona, Temirova (Indonesia Academia Research Society, 2024)
This study investigates the development of an efficient method for establishing virtual reality (VR) educational laboratories, focusing on enhancing teaching outcomes in technical fields exemplified through English classes. The integration of VR in technical education has been proven to improve learning efficiency, with studies showing a learning rate increase of 75-90% and a knowledge acquisition speed of up to four times faster. Despite these benefits, prolonged VR exposure can result in discomforts such as dizziness, eye strain, and cognitive fatigue. This study proposes a Fibonacci-based approach to structure VR learning sessions to address these challenges. By organizing session intervals according to the Fibonacci sequence and incorporating structured breaks, this method supports optimal cognitive processing, minimizes physical discomfort, and allows for smoother transitions between the virtual and real environments. A practical experiment involving 24 students was conducted to evaluate the effectiveness of this approach. The results revealed statistically significant improvements in learning outcomes and adaptation compared to traditional continuous VR sessions, with a p-value of less than 0.05. These findings suggest that the Fibonacci-based method offers a promising solution to the challenges associated with extended VR exposure in educational settings, enabling more effective and comfortable learning experiences. This approach holds potential for broader application in various technical fields, where VR serves as a tool for enhancing educational outcomes.